Tinjauan Yuridis Terhadap Sengketa Hak atas Tanah SMAN 1 Bandung: Analisis Kedudukan Hukum Hak Guna Bangunan dan Hak Pakai - Rahman, Naila Kamila; Elvira, Olga; Fatimah, Ghefira Nur; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The land dispute between SMAN 1 Bandung and the Perkumpulan Lyceum Kristen (PLK) is the main focus of this juridical analysis, highlighting the complexity of agrarian conflicts involving overlapping land rights between public and private interests. SMAN 1 Bandung bases its ownership on a Right-to-Use Certificate (Sertifikat Hak Pakai) issued by the National Land Agency (BPN) of Bandung City , while PLK claims its rights based on a historical Right-to-Build Certificate (Sertifikat Hak Guna Bangunan - SHGB) held by its predecessor, Het Christelijk Lyceum (HCL). This research employs a normative juridical method with statutory, case, and historical approaches to analyze the legal status of each right and the legal challenges faced by the government. The analysis shows that the Right-to-Use Certificate held by the government has valid and binding legal force based on the principle of presumption of legality (praduga rechtmatig), as long as it has not been annulled by a courth decision. On the other hand, PLK's historical claim presents challenges in the form of dual certificates and a burden of proof for the government. The solution for the government is to strengthen its arguments regarding the validity of the Right-to-Use Certificate, the principle of the social function of land for educational purposes, and the physical, bona fide possession of the land for decades.